IMPROVING THE PERFORMANCE OF EDUCATIONAL STAFF THROUGH EDUCATION, TRAINING, AND WORK DISCIPLINE: AN EMPIRICAL STUDY AT FACULTY OF ENGINEERING UNIVERSITAS SEBELAS MARET - Hastijani, Elijes; Almaidah, Siti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Employees have a significant impact on achieving organizational objectives, especially when they are competent and fulfill their duties effectively. It is crucial for companies and organizations to consider the factors influencing employee performance. This study aims to investigate the influence of education, training, and work discipline on the performance of academic staff at the Faculty of Engineering, Universitas Sebelas Maret. The sample comprises 78 individuals selected through sampling techniques. Analytical methods include exploratory testing, classical statistical mechanics testing, multiple regression analysis, and hypothesis testing. The findings indicate that education, professional training, and work discipline significantly contribute to the performance of education staff.